Charting the Rights of Community Health Workers in India: The Next Frontier of Universal Health Coverage - Janani Shanthosh; Andrea Durbach; Rohina Joshi (Harvard FXB Center for Health and Human Rights, 2020)
Community health workers (CHWs) have the capacity to bring essential health services to under-resourced communities. Globally, CHWs have made significant contributions to poverty alleviation, increased food security, and reductions in health inequalities. India's one million accredited social health activists (ASHAs), the largest cohort of CHWs in the world, have been credited with increasing the rate of institutional deliveries and the uptake of vaccinations. ASHAs operate at the margins of health systems and the formal health workforce, often due to misperceptions of their skills and discrimination based on gender, socioeconomic status, education, and rurality. The "voluntary" nature of their work can entrench their precarious status, which is characterized by a lack of access to employment rights, adequate remuneration, and institutional support. This article argues that the prioritization of the labor rights of CHWs in the design and implementation of the World Health Organization's 2018 Guideline on Health Policy and System Support to Optimize Community Health Worker Programmes can serve to ensure safe working conditions and freedom from discrimination, coercion, and violence. It further argues that the resultant enhancement and protection of CHWs' rights and long-term security provides an essential pathway for harnessing their potential to transform universal health coverage.